2022
DOI: 10.1177/15593258221120485
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals That Interfere With Drug Metabolism and Transport, Modifying Plasma Concentration in Humans and Animals

Abstract: Phytochemicals (Pch) present in fruits, vegetables and other foods, are known to inhibit or induce drug metabolism and transport. An exhaustive search was performed in five databases covering from 2000 to 2021. Twenty-one compounds from plants were found to modulate CYP3A and/or P-gp activities and modified the pharmacokinetics and the therapeutic effect of 27 different drugs. Flavonols, flavanones, flavones, stilbenes, diferuloylmethanes, tannins, protoalkaloids, flavans, hyperforin and terpenes, reduce plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 165 publications
1
6
0
Order By: Relevance
“…For their presence in our diet, PheCs are generally considered safe and usable, with no trouble for the design of new drugs. However, it should be underlined that PheCs may interact and interfere with many currently used conventional drugs, making their use not completely devoid of risks for some classes of patients [ 76 ]. In particular, Gómez-Garduño et al [ 76 ] reported that the interactions of PheCs with drugs often involve cytochrome CYP3A enzymes and P-gp transporters and are mediated through the regulation of gene expression or inhibitory effects on functional proteins that, ultimately, may modify plasma concentrations of drugs.…”
Section: Phecs Included In Drug Nanodelivery Systems For Tumor Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…For their presence in our diet, PheCs are generally considered safe and usable, with no trouble for the design of new drugs. However, it should be underlined that PheCs may interact and interfere with many currently used conventional drugs, making their use not completely devoid of risks for some classes of patients [ 76 ]. In particular, Gómez-Garduño et al [ 76 ] reported that the interactions of PheCs with drugs often involve cytochrome CYP3A enzymes and P-gp transporters and are mediated through the regulation of gene expression or inhibitory effects on functional proteins that, ultimately, may modify plasma concentrations of drugs.…”
Section: Phecs Included In Drug Nanodelivery Systems For Tumor Targetingmentioning
confidence: 99%
“…However, it should be underlined that PheCs may interact and interfere with many currently used conventional drugs, making their use not completely devoid of risks for some classes of patients [ 76 ]. In particular, Gómez-Garduño et al [ 76 ] reported that the interactions of PheCs with drugs often involve cytochrome CYP3A enzymes and P-gp transporters and are mediated through the regulation of gene expression or inhibitory effects on functional proteins that, ultimately, may modify plasma concentrations of drugs. These interactions are presumably related to the distribution of phytochemicals in circulation and, from there, to all our organs and tissues.…”
Section: Phecs Included In Drug Nanodelivery Systems For Tumor Targetingmentioning
confidence: 99%
“…Phytomolecules from herbal products, as well as bioactive phytochemicals from plant foods and food dressings, have potential health effects [1][2][3][4]. However, it is known that herbal products and nutraceuticals could affect drug-metabolizing enzymes and transporters [5,6].…”
Section: Phytomolecules-drug Interactions: Clinical and Nutritional I...mentioning
confidence: 99%
“…Cranberry juice administered to mice reportedly caused drug interactions with OATP (SLCO) substrates as well [73]. Other plant-based polyphenols have been reported to modulate the gene expression of ABCB1, altering P-gp levels and impacting drug bioavailability and the response of cancer cells to chemotherapeutic treatment [74][75][76][77]. Limited preclinical work also supports a role for cranberry extracts in increasing cisplatin sensitivity in ovarian cells, but without a linkage to transport mechanisms [78].…”
Section: Introductionmentioning
confidence: 99%